Determination of lactic acid bacteria isolated from the gastrointestinal tract of Bali cattle with potential probiotic role - Dewa Made Sukrama; I Wayan Suardana (Journal of Global Pharma Technology, 2018)
Bali cattle is known as pioneer’ cattle resulted by their high ability to adapt in poor quality of feed so that was assumed for finding the specific species of lactic acid bacteria. The study aimed to investigate the potency of lactic acid bacteria isolated from the gastrointestinal tract of Bali’ cattle as a candidate for new probiotic. Fifteen isolates of lactic acid bacteria isolated from 15 intestinal tracts of Bali cattle were grown on the specific medium deMan Rogosa Sharpe (MRS) broth followed by Gram staining, catalase test, the formation of CO2 gas, and antimicrobial activities against Bacillus cereus. The result of this study confirmed 15 isolates were Gram-positive bacteria, and 14 out of 15 isolates were categorized as homofermentative. Probiotic potency test showed 11 out of 15 isolates were tolerant against lower pH (pH 2, 4 and 6), and also resistant to bile acid with NaDC concentration 0.2, 0.4, and 0.6 mM. Identification of isolate using API 50CH test kit found 4 out of 5 isolates as Lactobacillus sp. and the remainder as Lactococcus sp. The study concluded isolates of lactic acid bacteria isolated from the gastrointestinal tract of Bali cattle showed potential as a probiotic candidate.